Isotopic abundance of 13 C and contribution of eucalyptus biomass to soil organic matter conversion - Severo,Fabiane Figueiredo (2017)
ABSTRACT: It has become possible to evaluate the conversion of soil organic matter (SOM) in pastures and arboreal crops due to the difference between the photosynthetic cycles of Eucalyptus (C3) and most grasses (C4). The auto analyzer method coupled to the IRMS (Isotope Ratio Mass Spectrometer) in the present study evaluated the 13C content in soil profiles of Eucalyptus plantations of different ages (2, 10 and 21 years), in natural regeneration areas and natural grazing fields, and estimated the SOM conversion of each crop type of. The initial management of all sampled areas was natural pasture. The following profile layers were evaluated: 0-5, 5-10, 10-20, 20-30, 30-40, 40-50, 50-70 and 70-90cm, and the contribution of Eucalyptus biomass over the years of farming was estimated in the SOM conversion process. After 2 years of planting Eucalyptus, the beginning of pasture carbon conversion process occurred in the surface layer (0-5cm). Ten years after planting, the process of converting organic matter by arboreal crops reached the layers up to 20cm. After 21 years of planting and in natural regeneration areas, the entire profile has already been changed by planting Eucalyptus and native tree species.